The president's assassin - Haig, Brian (New York : Warner Vision Books, 2006)
With just three days to prevent the assassination of the President, Army lawyer Sean Drummond races the clock in the high-stakes countdown of his career.
National College of Business and Arts
Keywords: Politicians -- Crimes against -- Fiction; Political fiction